THE ROLE OF YOUTH IN DIGITALIZING FALAK SCIENCE IN ISLAMICASTRO APPLICATIONS - Fajri Zulia Ramdhani (Fakultas Syari'ah dan Hukum UIN Walisongo, 2020)
This research starts from academic awareness when realizing Falak keyword in the Play Store. It shows fifteen Falak aplications by programmers without validated Falak competence.This is crucial, because Falak regulates not only astronomical or social relations, but also theological. One of these applications were developed by Falak youth, namely Muhammad Faishol Amin with his Islamicastro. This research discusses digitization of Falak by Islamicastro and youth Falak contributions. This research is qualitative type that based going exploring. Primary and secondary data collection is done by documentation and interviews. The research data is processed in three stages, codification, presentation, and conclusion drawing. Then data were analyzed with descriptive analysis and inductive thingking methods. The conclusion is Islamicastro helps Falak practitioners by his data accuracy in the field. From literatures, algorithm of Islamicastro uses the ephemeris method, the spherical astronomy, and the renewal of vincety method. Muhammad Faishol Amin are agents of change as UU No. 40 of 2009 whose part is anacted role, prescribed role, and role models.